(4-7i)=(3+6i)

Simple and best practice solution for (4-7i)=(3+6i) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4-7i)=(3+6i) equation:



(4-7i)=(3+6i)
We move all terms to the left:
(4-7i)-((3+6i))=0
We add all the numbers together, and all the variables
(-7i+4)-((6i+3))=0
We get rid of parentheses
-7i-((6i+3))+4=0
We calculate terms in parentheses: -((6i+3)), so:
(6i+3)
We get rid of parentheses
6i+3
Back to the equation:
-(6i+3)
We get rid of parentheses
-7i-6i-3+4=0
We add all the numbers together, and all the variables
-13i+1=0
We move all terms containing i to the left, all other terms to the right
-13i=-1
i=-1/-13
i=1/13

See similar equations:

| 2x-6-5(x+1)=3x+6 | | (3r-2)/8=2 | | 1 = 8 s 5 | | -22=-342+x | | -5c=c=3 | | 1/3d-5/6=2/9d+37/6 | | 5(7x-2)=92 | | 6x=2=26 | | x2=3x+4 | | 3x(2x+25)=180 | | 3.2=-04n | | -5cc=3 | | -4=2-2/5x | | 4x-4+3x=-32 | | 66÷6x2-1=x | | 3÷x-4=19 | | (3/5)g-(1/3)=(10/3) | | 68+25d=400+25d | | 2r+-1(5+r)=13+2r | | z−9=−12z−9=−12. | | 85-z=113 | | 8x+1=6-7x+4 | | 16x+3=(5+2x) | | F(x)=2x(x^2-4x-1) | | 2y-8y=20 | | x^2=-25x-100 | | (x-6)/5=7/12 | | −9−8x=−2(7+4x) | | 2f-10=6+1f | | 1/(4p)=-3 | | 2(x+1)÷1/2=x*1 | | 12=5.6y |

Equations solver categories